Exploring solution ICAR ATRP of methyl acrylate with AIBN as azo initiator: a kinetic modeling and simulation study - Guilherme C.L. Faria; Emerson P. Lyra (Results in Materials, 2022)
Supplementary techniques to atom transfer radical polymerization (ATRP) have been studied to reduce the concentration of catalytic complexes used, aiming at a less costly and more environmentally friendly process for synthesizing polymeric materials. Initiators for continuous activator regeneration ATRP (ICAR ATRP) is one technique in which a source of primary free radicals allows the reactivation of catalytic species used in the conventional ATRP. Due to the technological relevance of the topic, this work aims to expand the contribution to literature with kinetic modeling and simulation study for an ICAR ATRP system not yet explored. For this purpose, it was investigated solution ICAR ATRP of methyl acrylate with copper-based catalysts and azobisisobutyronitrile as ICAR initiator. The method of moments was employed to derive material balance equations. We find that the kinetic mechanism that best represented the trends of experimental data from literature was the one that considered specific side reactions of acrylates, such as backbiting and radical catalytic termination. In the model fitting procedure, a nonlinear optimization process had to be developed to estimate the values of kinetic rate constants not yet reported in the literature. The values obtained for the missing kinetic rate constants are consistent with similar experimental systems found in the literature. The deterministic model obtained was then employed to study the concentration profile maps. Simulations allowed verifying the slow release of primary free radicals from ICAR initiator to reduce the deactivators in activators species continuously. In addition, it was possible to confirm that the ICAR ATRP can be thermoregulated. Parametric analyses showed that variations in kinetic rate constants and reaction stoichiometry can shape monomer conversion and the molecular properties of the polymer (e.g., molecular weight, dispersity, and end functionality).